The global capacity of Belgium’s major cities: Antwerp and Brussels compared - Ben Derudder; Peter J. Taylor (Belgeo, 2003)
The paper has two purposes: (i) to outline a methodology for systematically measuring economic relations between the world’s major cities and (ii) to provide a general assessment of the position of Belgium’s major cities in this global urban network. In the first section, we stress that research on Brussels and Antwerp under conditions of contemporary globalization lacks a systematic account of their global relational patterns, a knowledge lacuna that can at least partly be traced back to the dearth of suitable data. In a second section, we outline the methodology for measuring the networked context of the world’s major cities. In a third section, we provide a systematic overview of Antwerp’s and Brussels’ position in this global urban network. Apart from the rather common sensical observation that Brussels is more strongly connected than Antwerp, it is also shown that Brussels’ «global» relations contrast with Antwerp’s more intense «local» relations. In relative terms, Brussels is strongly connected to East Asia and North America, while the most thorough links of Antwerp are exclusively with nearby European (especially German) cities.